Control of Zonocerus variegatus with ULV formulation of Metarhizium flavoviride conidia - Douro-Kpindou, O.K.; Godonou, I.; Houssou, A.; Lomer, C.J.; Shah, P.A. (Informa UK Limited, 1995)
An oil-based formulation of Metarhizium flavoviride conidia, applied at 2 1012 spores ha-1 in 1 l ha-1 gave good control of Zonocerus variegatus in 1-ha plots in southern Benin. In a three-replicate, randomized, complete block (RCB) trial in Mono province, a significant reduction in insect counts between treated and control plots was observed 10-15 days after application; treatment reduced the population by about 90%. A four-replicate RCB trial in Oue me province also gave high mortality. Although a significant difference between treated and untreated plots was observed 10-18 days after application, insect dispersal out of cassava fields towards oviposition sites interfered with a clear demonstration of control. Significantly more Z. variegatus cadavers with M. flavoviride infection were found in treated plots than control plots.